2010
DOI: 10.1007/s12633-010-9044-9
|View full text |Cite
|
Sign up to set email alerts
|

Resin Bonding to Silicatized Zirconia with Two Isocyanatosilanes and a Cross-linking Silane. Part I: Experimental

Abstract: In this study we have investigated the effects of the chain length of hydrolyzable groups in two isocyanato silane coupling agents, 3-isocyanatopropyltrimethoxysilane and 3-isocyanatopropyltriethoxysilane, on the shear bond strength of resin attached to silicatized zirconia. In addition, the effects of varying the silane concentration (at 0.1 vol% and 1.0 vol%) with or without the addition of a cross-linking silane (0.05 vol % or 0.5 vol% bis-1,2-(triethoxysilyl)ethane) were assessed. It was concluded that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The experimental results reported in "Part I: Experimental" [4] have been explained in terms of reaction mechanisms and conceptual diagrams. It can be concluded and suggested that the shear bond strength between resin cement and silicatized zirconia depends on the following:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results reported in "Part I: Experimental" [4] have been explained in terms of reaction mechanisms and conceptual diagrams. It can be concluded and suggested that the shear bond strength between resin cement and silicatized zirconia depends on the following:…”
Section: Discussionmentioning
confidence: 99%
“…Results from our study of the effects of using silanes with hydrolyzable alkoxy groups, adding a cross-linking silane and using silanes with different organofunctional groups on the shear bond strength between resin and silicatized zirconia were reported in "Part I: Experimental" [4]. In this study, an approach to explain the experimental results by means of a series of proposed reaction mechanisms are discussed and presented in conceptual diagrams.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Sandblasting was performed using Rocatec Sand Plus (110 μm of silicacoated alumina particles; 3M ESPE) at a constant pressure of 280 kPa for 30 s/cm 2 and at a perpendicular distance of 10 mm, according to standard procedure in dental laboratories 14) . Sandblasted zirconia samples were then ultrasonically cleaned in 70% ethanol for 10 min.…”
Section: Silica-coating Of Zirconia By Sandblastingmentioning
confidence: 99%
“…After SBS testing, failure mode of each sample was assessed using a light microscope (NZ6, Leica, Wetzlar, Germany). Failure modes were classified as follows: 'adhesive failure' when less than 33% of resin composite remained on substrate surface; 'mixed failure 'when more than 33% but less than 66% of resin composite remained on substrate surface; and 'cohesive failure' when the remaining amount was more than 66% 14) .…”
Section: Shear Bond Strength Measurementmentioning
confidence: 99%